Integrated solid waste management: a life cycle assessment - Othman, Norazli (Asian Research Publishing Network, 2015)
An amount of 30, 000 tonnes per day is expected to be accumulated in Malaysia in the near year 2020. In order to manage this increasing volume of solid wastes, the waste management technologies have to be further integrated between one and another. A life cycle assessment is an environmental management tool to project and compare the environmental impacts of a product or a service from the initial stage until the final stage of the product's or the service's life-cycle. Life cycle assessment checks every part in a system in which the input such as raw materials and energy and the output such as products including the emissions of air, water and residuals of the system are calculated in order to project the existing environmental impacts resulting from the system's activities. This paper discusses the application of the technique as a tool to predict the integrated solid waste management system impacts towards the environment. The environmental effect analysis on the case study has found that the practiced management scenario i.e. integrated solid waste management is able to solve issues related to the reduction of world's energy resources and raw materials. However, a little impact has been given by the system with regards to the rise of the global warming effects due to the transportation and material processing activities. The improvement of the integrated solid waste management system in future is required in order to reduce the environmental burden that produced the global warming effects